2021
DOI: 10.1016/j.omtn.2021.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an HCC recurrence model based on the investigation of immune-related lncRNAs and related mechanisms

Abstract: Long noncoding RNAs (lncRNAs) are emerging as critical regulators of gene expression and play fundamental roles in immune regulation. Growing evidence suggests that immunerelated genes and lncRNAs can serve as markers to predict the prognosis of patients with cancers, including hepatocellular carcinoma (HCC). This study aimed to contract an immunerelated lncRNA (IR-lncRNA) signature for prospective assessment to predict early recurrence of HCC. A total of 319 HCC samples under radical resection were randomly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…For example, a 3-lncRNA signature by Gu et al could well predict both recurrence free survival and overall survival in small HCC patients [ 76 ], a 15-lncRNA classifier by Zhang et al effectively identified HCC recurrence [ 77 ], a 7-lncRNA classifier by Lv et al predict early recurrence within 2 years after surgical resection for HCC [ 78 ]. The prognostic performance of this 4-lncRNA signature is comparable to other developed lncRNA-based signatures [ 76 80 ], while the differences of selected lncRNAs in each lncRNA-based signature might be due to the specific feature gene selection strategy and different training set. Moreover, the combined model of the 4-lncRNA signature risk score, AFP and TNM stages further improve the 2-year DFS prediction with an AUC of 72.02%.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, a 3-lncRNA signature by Gu et al could well predict both recurrence free survival and overall survival in small HCC patients [ 76 ], a 15-lncRNA classifier by Zhang et al effectively identified HCC recurrence [ 77 ], a 7-lncRNA classifier by Lv et al predict early recurrence within 2 years after surgical resection for HCC [ 78 ]. The prognostic performance of this 4-lncRNA signature is comparable to other developed lncRNA-based signatures [ 76 80 ], while the differences of selected lncRNAs in each lncRNA-based signature might be due to the specific feature gene selection strategy and different training set. Moreover, the combined model of the 4-lncRNA signature risk score, AFP and TNM stages further improve the 2-year DFS prediction with an AUC of 72.02%.…”
Section: Discussionmentioning
confidence: 81%
“…Kaplan-Meier plot confirmed that the 4-lncRNA signature could successfully classified HCC patients into the low- and high-risk groups and predict early recurrence. Several previous developed lncRNA-based signatures were reported for HCC survival prediction and showed better performance than clinicopathological factors [ 76 80 ]. For example, a 3-lncRNA signature by Gu et al could well predict both recurrence free survival and overall survival in small HCC patients [ 76 ], a 15-lncRNA classifier by Zhang et al effectively identified HCC recurrence [ 77 ], a 7-lncRNA classifier by Lv et al predict early recurrence within 2 years after surgical resection for HCC [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three identified genes were associated with fibrosis and potentially modulated by transforming growth factor beta, platelet-derived growth factors, sonic hedgehog protein, or Notch pathways[ 97 ]. Given the emerging evidence suggesting that lncRNAs participate in cancer immunity, another study used RNA-seq to look at immune-related lncRNAs and related mechanisms from the TCGA database, identifying nine immune-related lncRNAs associated with HCC recurrence via Cox regression analysis[ 98 ]. The authors also created a recurrence prediction model based on their findings that was validated in an independent patient cohort.…”
Section: Rna-seq Analysis Of Recurrent Hccmentioning
confidence: 99%
“…The clinical characteristics included age, gender, pathology grade and TNM stage. The performance of the combined nomogram was evaluated by calibration plot using bootstrap method (21). And the time-ROC curve was performed to compare the prediction value among the combined nomogram model, IMPS, and clinical characteristics.…”
Section: Construction and Evaluation Of The Combined Nomogram Conside...mentioning
confidence: 99%